Peningkatan Kemampuan Memorizing Siswa dengan Menggunakan Flashcard pada Pembelajaran Pendidikan Agama Islam dan Budi Pekerti - Risda Fatma Aisah; Novianora Nasution; Shofi Alawiyah; Sakinah Sakinah (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to improve students’ memorization skills on the topic of Al-Asma Al-Husna through the use of flashcard media in Islamic Religious Education and Character Education learning for Grade VII students at SMP Negeri 2 Panyabungan. The method used is Classroom Action Research (CAR) consisting of two cycles, each including planning, action, observation, and reflection stages. The research subjects were 37 students of class VII (5). Flashcards are cards of a certain size containing words, symbols, or other visual elements; they are designed for quick learning. Data were collected through oral tests, interviews, observations of student and teacher activities, and documentation. The results of the study showed a significant improvement. Cycle I: The average pre-test score of 59 increased to 63.64 in the post-test, which was categorized as low. Cycle II: The average post-test score reached 82.16, categorized as moderate. Students’ activeness and learning mastery also increased, as indicated by the percentage of students achieving the Minimum Mastery Criteria (KKM) of 72, which rose from 8.11% in Cycle I to 100% in Cycle II. The conclusion of the study proves that flashcard media is effective in improving students’ memorization skills in Islamic Religious Education and Character Education learning.